Genome-Wide Analysis of the Fasciclin-Like Arabinogalactan Protein Gene Family Reveals Differential Expression Patterns, Localization, and Salt Stress Response in Populus - Zang, Lina; Zheng, Tangchun; Chu, Yanguang; Ding, Changjun; Zhang, Weixi; Huang, Qinjun; Su, Xiaohua (Frontiers in Plant Science, 2015)
Fasciclin-like arabinogalactan proteins (FLAs) are a subclass of arabinogalactan proteins (AGPs) involved in plant growth, development and response to abiotic stress. Although many studies have been performed to identify molecular functions of individual family members, little information is available on genome-wide identification and characterization of FLAs in the genus Populus. Based on genome-wide analysis, we have identified 35 Populus FLAs which were distributed on 16 chromosomes and phylogenetically clustered into four major groups. Gene structure and motif composition were relatively conserved in each group. All the members contained N-terminal signal peptide, 23 of which included predicted glycosylphosphatidylinositol (GPI) modification sites and were anchored to plasma membranes. Subcellular localization analysis showed that PtrFLA2/20/26 were localized in cell membrane and cytoplasm of protoplasts from Populus stem-differentiating xylem. The Ka/Ks ratios showed that purifying selection has played a leading role in the long-term evolutionary period which greatly maintained the function of this family. The expression profiles showed that 32 PtrFLAs were differentially expressed in four tissues at four seasons based on publicly available microarray data. 18 FLAs were further verified with qRT-PCR in different tissues, which indicated that PtrFLA1/2/3/7/11/12/20/21/22/24/26/30 were significantly expressed in male and female flowers, suggesting close correlations with the reproductive development. In addition, PtrFLA1/9/10/11/17/21/23/24/26/28 were highly expressed in the stems and differentiating xylem, which may be involved in stem development. To determine salt response of FLAs, qRT-PCR was performed to analyze the expression of 18 genes under salinity stress across two time points. Results demonstrated that all the 18 FLAs were expressed in root tissues; especially, PtrFLA2/12/20/21/24/30 were significantly induced at different time points. In summary, this study may lay the foundation for further investigating the biological functions of FLA genes in Populus trichocarpa.